The Famous Five. Five get into trouble - Blyton, Enid (Hodder Children's London, 2010)
This story follow the exploits of Julian, Dick, Anne, George and Timmy their faithful and clever dog. Dick has been kidnapped, mistaken for someone else, and the Famous Five are frantic! Desperately, they track him down to a sinister old house in the middle of nowhere - and he's safe and well! But just when they thought their troubles were over, the gang find themselves held captive and in terrible danger! Who will come for them now?